Reduction in Aggregation of Insulin Through Conformational Stabilization by Glucose - BARZEGAR, A.; AMINBAKHSH, M.; Hosseinpour Faizi, M.A.; PANAHI, Y.; AZARFAM, P.; POULADI, N.; CHAPARZADEH, N.; MOOSAVI-MOVAHEDI, A.A. (Asian Journal of Chemistry, 2010)
Aggregation of insulin molecule remains a serious obstacle in the development of alternative methods of diabetes therapy. To reduce the insulin's aggregation process and increase in structural stability, the effects of glucose were studied by UV, fluorescence, and circular dichroism spectroscopy as well as by urea denaturation study in phosphate buffer, pH 7.5. The results show a decrease in aggregation of insulin and increase in midpoint of urea denaturation curve in case of incubation with glucose effectively at 3 fold concentrations relative to insulin ([glucose]/[insulin] = 3). Therefore the results indicate that incubation of insulin with glucose improve its physical and structural stability.